El rol mediador de la soledad social en la relación entre inteligencia emocional y soledad emocional en adolescentes peruanos - Angulo Salas, Roger Joaquin (2024)
The present research proposed a mediation model between emotional intelligence and emotional loneliness. The objective was to analyse the mediating role of social loneliness in the relationship between emotional intelligence and emotional loneliness in secondary school students of a regular basic education institution in the city of Parcona in Ica, southern Peru. The study has an explanatory and cross-sectional design, and the participants consisted of 731 secondary school adolescents. The Jong-Gierveld Loneliness Scale (ESJG) and the Trait Meta-cognition of Emotional States Scale (TMMS-24) were used. Psychometric validation of the instruments was carried out through Confirmatory Factor Analysis (CFA), and evidence of reliability was obtained through the alpha and omega coefficient with acceptable values. Data analyses were performed using structural equation modelling (SEM) to represent the statistical mediation model with observable variables. The results reported complete mediation by finding statistical significance in the effect of emotional intelligence on emotional loneliness mediated by social loneliness (p< .001), and not in the direct pathway of the effect of emotional intelligence on emotional loneliness (p=0.35). In conclusion, emotional intelligence does not directly reduce emotional loneliness, but first decreases social loneliness, which then leads to a reduction in emotional loneliness. Therefore, in order to reduce emotional loneliness, it is key to intervene in aspects related to social loneliness.